2012
DOI: 10.1111/j.1745-4549.2012.00740.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Cooking Methods on Lipid Oxidation and Microbial Quality of Vacuum-Packaged Emulsion Products from Chicken

Abstract: The aim of this work was to study the effect of different cooking methods viz, moist cooking (nuggets), dry cooking (patties) and deep‐fat frying (croquettes) on lipid oxidation and microbial quality of few emulsion‐based meat products from chicken under vacuum packaging conditions during refrigerated storage. When different cooking methods were studied, croquettes were the most affected (P < 0.05) by lipid oxidation as indicated by thiobarbituric acid reactive substances, peroxide value and free fatty acids c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 29 publications
4
15
0
Order By: Relevance
“…However, on day 21 of storage, control samples had higher ( P < 0.05) FFA values than all treated samples. The FFA levels observed in the present study are similar to the values reported by Naveena et al . for chicken nuggets and patties.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…However, on day 21 of storage, control samples had higher ( P < 0.05) FFA values than all treated samples. The FFA levels observed in the present study are similar to the values reported by Naveena et al . for chicken nuggets and patties.…”
Section: Resultssupporting
confidence: 92%
“…This reduction in peroxide value in antioxidant‐treated samples can be attributed to the antioxidant activity of phenols preventing peroxide formation during storage. The peroxide values observed in the present study are similar to those reported by Naveena et al . for chicken nuggets and patties.…”
Section: Resultssupporting
confidence: 92%
“…This is due to the great nutritional value and a high level of polyunsaturated fatty acids compared to red meat, which has a remarkable effect on health [Khaksar et al, 2010]. In addition, poultry products are universally accepted, because they are not subject to cultural or religious constraints [Naveena et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…The first one is when croquette-filling dough is divided and formed in units, after cooling. The recontamination could be due to the high handling of dough, with certain contact with equipment surfaces and air passing through human respiration and skin [88]. The second critical point is the application of batter or binder solution (by immersion or shower) to facilitate adhesion of breadcrumbs on the croquette units surface.…”
Section: Microbial Safetymentioning
confidence: 99%
“…Onion, garlic, oil, salt, spices, powdered milk, milk whey, starch, shellfish, béchamel sauce, potatoes and water can be other dough ingredients. The difference between these croquettes and nuggets (or meat analogue nuggets) or patties is that the main and minor ingredients are boiled along with wheat flour and milk (or milk powder and water; or white sauce) [4,9,58,88,95] for obtaining a tied and consistent croquette dough, but at the same time juicy.…”
Section: Introductionmentioning
confidence: 99%